Inorganic chemistry - House, James E (Academic Press, 2020)
Inorganic Chemistry, Third Edition, provides essential information for students of inorganic chemistry and is updated throughout. The presentation of topics is made with an effort to be clear and concise so that the book is portable and user friendly. The text emphasizes fundamental principles - including molecular structure, acid-base chemistry, coordination chemistry, ligand field theory, and solid state chemistry. It is organized into five major themes (structure, condensed phases, solution chemistry, main group and coordination compounds) with several chapters in each. There is a logical progression from atomic structure to molecular structure to properties of substances based on molecular structures, to behavior of solids, etc. The textbook contains a balance of topics in theoretical and descriptive chemistry. For example, the hard-soft interaction principle is used to explain hydrogen bond strengths, strengths of acids and bases, stability of coordination compounds, etc. Discussion of elements begins with survey chapters focused on the main groups, while later chapters cover the elements in greater detail. Each chapter opens with narrative introductions and includes figures, tables, and end-of-chapter problem sets. This new edition features updates throughout, with an emphasis on bioinorganic chemistry and a new chapter on nanostructures and graphene. More in-text worked-out examples encourage active learning and prepare students for their exams. This text is ideal for advanced undergraduate and graduate-level students enrolled in the Inorganic Chemistry course. This core course serves Chemistry and other science majors. The book may also be suitable for biochemistry, medicinal chemistry, and other professionals who wish to learn more about this subject area"-- Provided by publisher.